The effect of Sales Tax on Luxury Goods (PPnBM), Value Added Tax (VAT), and progressive rates on consumer purchasing power in four-wheeled motor vehicles - Amelia, Tresya; Ismanto, Juli (WIM Solusi Prima, 2025)
This study aims to analyze the influence of Luxury Goods Sales Tax (LGST), Value Added Tax (VAT), and Progressive Tax Rates on Consumer Purchasing Power. The population in this study consists of four-wheeled motor vehicle consumers at SAMSAT Serpong in 2024. Primary data was used, with a total of 100 respondents selected using the Slovin formula. The data analysis techniques employed include descriptive statistical analysis, validity and reliability tests, multiple linear regression, coefficient of determination, and hypothesis testing. SPSS version 26 was used for quantitative data analysis. The results indicate that LGST has a significant effect on consumer purchasing power, with a significance level of 0.004 which is smaller than 0.05. VAT also significantly affects consumer purchasing power, with a significance level of 0. which is smaller than 0.05. Similarly, Progressive Tax Rates have a significant impact, with a significance level of 0.032 which is smaller than 0.05.